1998
DOI: 10.1007/s002709900253
|View full text |Cite
|
Sign up to set email alerts
|

Aortoiliac aneurysm with arteriocaval fistula treated by a bifurcated endovascular stent-graft

Abstract: A 71-year-old patient with high-output cardiac failure was found to have an aneurysmal distal aorta with evidence of an arteriocaval fistula on ultrasound scanning. CT demonstrated an aneurysm of the distal aorta and right common iliac artery and an intraarterial digital subtraction angiogram confirmed an arteriocaval fistula. In view of the patient's cardiac failure and general condition an endovascular stent was considered. The right internal iliac artery was occluded with Tungsten coils prior to the inserti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 5 publications
0
38
0
Order By: Relevance
“…This presentation accounts for 2e4% of acute AAA rupture. 1 In this circumstance, the physiologic consequence is that of venous hypertension that can lead to various clinical sequelae. One of these is increased venous return to the heart with fluid overload and high output cardiac failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This presentation accounts for 2e4% of acute AAA rupture. 1 In this circumstance, the physiologic consequence is that of venous hypertension that can lead to various clinical sequelae. One of these is increased venous return to the heart with fluid overload and high output cardiac failure.…”
Section: Discussionmentioning
confidence: 99%
“…Aorto-caval fistula (ACF) is a rare presentation of ruptured AAA occurring in 2e4% of acute AAA rupture. 1 The physiologic changes associated with ACF differ from isolated hypotension and shock associated with typical AAA rupture. Rapid diagnosis and treatment offer the best chance of survival.…”
mentioning
confidence: 99%
“…This is a common problem with such lesions. Endovascular repair of an aorto-caval fistula has been a therapeutic option since 1998 [4]. However, the only case series describing endovascular treatment of aorto-caval fistulae showed a complicated clinical picture, with a mortality rate of 75% [5].…”
Section: Discussionmentioning
confidence: 99%
“…At the dawn of the endovascular age, most ACF had been repaired primarily in an open fashion and the literature accounted the surgical mortality to be as high as 16–66%. 4,5 However, after Beveridge et al 6 in 1998 reported the first endovascular repair of ACF, many have published reports of ACF describe endovascular management. We sought to review the contemporary outcomes and complications of both methods, present a successful case of open repair, and determine if endovascular repair was associated with improved outcomes.…”
Section: Introductionmentioning
confidence: 99%